Effects of alkali-treated agricultural residues on nitrate removal and N2O reduction of denitrification in unsaturated soil. (15th May 2018) - Sun, Zhaoyue; Zheng, Tianyuan; Xin, Jia; Zheng, Xilai; Hu, Rongting; Subhan, Fazle; Shao, Haibing
Abstract: Lignocellulosic agricultural residues were utilized as denitrification carbon substrates to improve the purification capacity of unsaturated soil and alleviate nitrate pollution of groundwater. In this study, corncob and wheat straw were treated by calcium hydroxide to improve biodegradability and enhance denitrification potential. Calcium hydroxide treatment decreased the contents of lignin (i.e., from 16.7 wt% to 15.2 wt% in corncob and from 21.9 wt% to 20.6 wt% in wheat straw), increased potential biodegradable carbon by 4.4–5.3 times, reached complete nitrate removal 7–14 days earlier and decreased N2 O/(N2 O+N2 ) ratios by 85–99%. The results provide an insight into the application of alkali-treated agricultural residues as denitrification carbon sources to alleviate nitrate transport to groundwater and reduce potential greenhouse effect. Highlights: Corncob and wheat straw were treated with Ca(OH)2 to improve biodegradability. Alkali-treated agricultural residues could increase N O 3 − -N removal performance. Alkali-treated agricultural residues could reduce N2 O/(N2 +N2 O) ratios. The relative abundance of nosZ in soil increased with treated carbon substrates addition.